2006
DOI: 10.1016/j.im.2006.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Sharing and access right delegation for confidential documents: A practical solution

Abstract: Follow this and additional works at: http://aisel.aisnet.org/acis2004This material is brought to you by the Australasian (ACIS) at AIS Electronic Library (AISeL Abstract This paper addresses a practical problem in Document Management Systems for which no existing solution is available in the market. To store confidential documents in a Document Management System, a common approach is to keep only the encrypted version of the documents to ensure the confidentiality of the contents.However, how to share these e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Not aligning the security plan with strategic information systems planning may lead to ineffective information security policy formulation (Doherty and Fulford, 2006). The security policy on sharing access rights is critical to designing secured mobile ES (Yiu et al , 2006). The policy on who must access or modify what needs to be clear to prevent any unauthorized access to ES.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Not aligning the security plan with strategic information systems planning may lead to ineffective information security policy formulation (Doherty and Fulford, 2006). The security policy on sharing access rights is critical to designing secured mobile ES (Yiu et al , 2006). The policy on who must access or modify what needs to be clear to prevent any unauthorized access to ES.…”
Section: Literature Reviewmentioning
confidence: 99%
“…93 The key for Hong Kong to win this race is to face up to the risks of cryptoassets and explore ways to establish a robust regulatory regime. 94…”
Section: Regulation Instead Of Prohibitionmentioning
confidence: 99%
“…It is observed that document processing is a highly collaborative process. Thus, Document management systems [6] are specially designed for handling and managing documents with the utmost care and efficiency. In such systems, documents are usually stored in file systems for ease and efficient retrieval.…”
Section: Introductionmentioning
confidence: 99%